Thermal management improvement of a liquid cooled Proton exchange membrane fuel cell through adoption of Al2O3 nanofluids as cooling medium / Irnie Azlin @ Nur Aqilah Zakaria - Zakaria, Irnie Azlin @ Nur Aqilah (Institute of Graduate Studies, UiTM, 2016)
So Proton Electrolyte Membrane Fuel Cell (PEMFC) has started to gain global attention nowadays due to the greener aspect of this technology with almost 90 % emission reduction as compared to internal combustion engine. However, in order to improve the thermal performance efficiency of a PEM fuel cell, an excellent thermal management system acquisition is strongly required. This study hybridized nanofluids and PEM fuel cell technologies into cooling medium of PEM fuel cell in order to improve the thermal management. To author’s knowledge, experimental study of nanofluids in an electrically active heat transfer device such as PEM fuel cell is almost none. The study focuses on Alumina oxides (Al2O3) nanofluids characterization, understanding heat transfer and fluid flow behaviour of Al2O3 nanofluids in a single cooling plate and later on establishing thermo electrical and thermo fluid performance of a fullscale PEM fuel cell with the adoption of Al2O3 nanofluids as the cooling medium. In this study, Al2O3 nanofluids with volume concentration of 0.1, 0.3 and 0.5 volume % have been dispersed in base fluids of water and two mixtures of water and ethylene glycol (EG), which are 60:40 and 50:50 (W:EG). Critical thermo-physical properties of nanofluids mainly electrical conductivity, viscosity and thermal conductivity were measured. Prandtl number and Thermo-electrical conductivity (TEC) ratio were established…